Nearshore to Offshore Trends in Plankton Assemblage and Stable Isotopes in Reefs of the West Philippine Sea - Yñiguez, Aletta T.; Apego, Gianina Cassandra May; Mendoza, Norman; Gomez, Norchel Corcia; Jacinto, Gil S. (Frontiers in Marine Science, 2022)
Coral reefs are typified by their benthic components, and reef diversity and productivity are traditionally ascribed to the symbiotic association between corals and zooxanthellae, and other macroalgal forms. Less understood is the role of plankton and adjacent pelagic areas in contributing to reef productivity. Half of the reef benthos are filter or particle feeders, while a significant proportion of reef fishes are planktivorous. These organisms can serve as bridges between adjacent oceanic areas to the reef proper, and the pelagic and benthic realm. Here, we investigate the plankton trophic dynamics in two reef systems in the West Philippine Sea. Physico-chemical data, phytoplankton and mesozooplankton samples were collected from stations spanning offshore to reef areas per site. These were subjected to microscopic and stable isotope analysis to determine variability in plankton distribution, phytoplankton and zooplankton interactions, and gain insights into the trophic dynamics and productivity of reefs. Results showed that there were distinct variations in plankton biomass and assemblage from offshore to reef areas, as well as between the reef systems. Phytoplankton distributions pointed towards filtering out of cells across the fore reef and reef flat areas, while mesozooplankton distributions could be mediated more by other factors. Isotopic signatures of δ13C and δ15N indicated the influence of different nutrient sources for phytoplankton and that mesozooplankton relied only partly on phytoplankton for food in most areas of the reefs. The mesozooplankton likely also obtain food from other sources such as the microbial and detrital pathways. More in-depth spatio-temporal studies on these bentho-pelagic interactions are recommended which can provide more robust estimates of the trophic dynamics of these reefs that are situated in important fishing grounds and key biodiversity areas.